2020
DOI: 10.1002/jgm.3153
|View full text |Cite
|
Sign up to set email alerts
|

miR‐647 inhibits glioma cell proliferation, colony formation and invasion by regulating HOXA9

Abstract: Background MicroRNA‐647 (miR‐647) has been reported to regulate tumor development, although its role in glioma remains unclear. Methods miR‐647 expression in glioma cells and normal cells was measured using a quantitative real‐time polymerase chain reaction. The effects of miR‐647 expression on glioma cell proliferation, cell apoptosis, colony formation and cell invasion were measured using a cell counting kit‐8 assay, flow cytometry, a colony formation assay and a transwell invasion assay. Luciferase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Due to previous reports, miR-647 could retard tumor progression via inhibiting downstream oncogenes (Ye et al, 2017;Qin et al, 2020). We subsequently discovered that overexpression of miR-647 promoted PCa cells proliferation and migration, which indicated that miR-647 act as a tumor inhibitor role in PCa (Figures 3G,H).…”
Section: Circnolc1 Upregulates Paqr4 Expression Through Sponging Mir-647mentioning
confidence: 81%
See 1 more Smart Citation
“…Due to previous reports, miR-647 could retard tumor progression via inhibiting downstream oncogenes (Ye et al, 2017;Qin et al, 2020). We subsequently discovered that overexpression of miR-647 promoted PCa cells proliferation and migration, which indicated that miR-647 act as a tumor inhibitor role in PCa (Figures 3G,H).…”
Section: Circnolc1 Upregulates Paqr4 Expression Through Sponging Mir-647mentioning
confidence: 81%
“…Thus, we screened and validated the interaction between circNOLC1 and miRNAs by circRNA pulldown and dual-luciferase reporter assay, results demonstrated that circNOLC1 function as a sponge of miR-647. Meanwhile, miR-647 was identified as a tumor inhibitor in glioma and gastric cancer (Ye et al, 2017;Qin et al, 2020). Whereas, its role in PCa remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, recent studies demonstrate abnormal HOXA9 expression in human AML, 9 colorectal cancer, 10 malignant glioma, 11 lung cancer, 12 and other tumours. This protein plays an important role in tumour progression (including metastasis), and is closely associated with prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…Each cluster contains between nine and 13 gene loci, which are regulated by highly conserved transcription factors; stringent control is essential given that these genes represent major regulators of embryonic development and cell differentiation. 6 , 7 A member of the HOX gene family, HOXA9 has recently been demonstrated to exhibit increased expression in a variety of human malignant tumours (including acute myeloid leukaemia (AML), 8 colorectal cancer (CRC), 9 malignant glioma, 10 lung cancer, 11 and is closely associated with tumour progression, invasion, metastasis, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the top 30 miRNAs, only miR-647 has been previously reported to show involvement in tumor progression. [10][11][12] To validate this, we conducted luciferase reporter assays and found that transfection of miR-647 mimics reduced the luciferase activity of the wild-type ZFAS1 reporter gene, but not the mutant ZFAS1 (ZFAS1-mut) ( Figure 4B and C). Moreover, we carried out a MS2-binding protein (MS2bp)-MS2-binding sequences (MS2bs)-based RIP (MS2-RIP) according to the previous studies.…”
Section: Zfas1 Interacts With Mir-647 In CCmentioning
confidence: 91%